Ireland, broadcasting and the spectrum wars. (1st March 2020) - Murphy, Kenneth
This article offers an overview and evaluation of Ireland's changing media landscape through the prism of the recent policy contestation surrounding the future use of the UHF spectrum and its implications for the medium of television broadcasting. The article brings into focus current policy and governance developments and their interplay with market and technological change and how they are shaping a small open European state's adaptation to the increasingly complex national/global hybrid media ecosystem. It examines the contexts surrounding the competition for spectrum resources and its implications for the role of free-to-air broadcasting and mobile broadband technologies in the future delivery of media and communication services. It takes a political economy and institutionalist perspective to evaluate the extent to which the evolution of the Irish institutional framework regarding broadcasting and broadband development and the allocation of spectrum frequencies is shaped by broader political economic and political/institutional dynamics and what this means for the remediation of broadcasting within the evolving digital media ecology.